(untitled) (Swiss Medical Weekly, 2022)
Zoonotic species of the Chlamydiaceae family should be considered as rare pathogenic agents of severe atypical pneumonia. A fatal case of a severe pneumonia due to Chlamydia psittaci was traced back to pet birds, and pneumonia in a pregnant woman was attributed to abortions in a sheep and goat flock, being the source of Chlamydia abortus. The two SARS‑CoV‑2-negative pneumonia cases presented here were investigated in an inter-disciplinary approach involving physicians and veterinarians. State-of-art molecular methods allowed the identification and genotyping of zoonotic Chlamydiae.